Comparing lexical bundles in medical research article abstracts of Iranian and foreign journals - Varghaei, Elshan; Khodadadi, Golsa (Penerbit Universiti Kebangsaan Malaysia, 2022)
The art of persuasive speaking or writing in English academic settings depends on using multi-word expressions, also known as clusters, collocations, or lexical bundles, to a large extent. They are discipline-specific prefabricated word combinations that statistically tend to appear together. However, many novice foreign writers of English have difficulty using appropriate discipline-bound lexical bundles, which has made numerous applied linguists in English for Academic Purposes (EAP) study the genre of research articles from this perspective. Thus, the present study sought to compare the similarities and differences of four-word lexical bundles in a 409210-word corpus of Medical Research Article (MRA) abstracts from Iranian and foreign journals. To accomplish this, in a frequency-based approach, bundles were extracted utilizing the AntConc3.5.7 concordance program, and their structures and functions were analyzed by Biber et al.'s (1999) structural and Hyland's (2008a) functional taxonomies. The results showed similarities in the distribution of the bundles’ main structural and functional patterns. However, besides the differences in the distribution of sub-structures and sub-functions, it was revealed that highly frequently shared lexical types in MRA abstracts of Iranian journals were less frequent in MRA abstracts of foreign journals and vice versa. This study helps novice medical researchers write unified abstracts which have a crucial role in getting research articles accepted or rejected. Furthermore, producing well-organized abstracts in internal Iranian journals can significantly enhance the rank of Iranian medical journals worldwide.